Penyuluhan Penguatan Fungsi Pekarangan Rumah Dalam Peningkatan Ketahanan Pangan Keluarga Pada Masa Pandemi Covid - 19 - Aryanti Setyaningsih; Wahyu Dwi Agussafutri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Food fulfillment at the household level is related to the level of household food security. The existence of the Covid-19 pandemic condition causes limitations in meeting sufficient food for each individual in the family. The inability of individuals and households to provide adequate, nutritious, and safe food is a risk factor of food insecurity, which has an impact on nutritional status problems. The purpose of this activity is to realize food security and family nutrition independently through optimizing the use of house yard with the aim of supporting the improvement of family health status. The method of implementing this service activity is by counseling families in the context of utilizing the function of the yard as a source of family food to increase the availability of family food and as an effort to improve family nutrition. This activity is to increases the knowledge, awareness, and motivation of the people of RW 09 Tlogosari Kulon to be able to realize family food security independently and as an effort to improve the nutritional status and health status of the family, especially during the Covid-19 pandemic.